PERFORMANCE SUPERVISION IN REALIZING THE DEVELOPMENT GOALS OF REGIONAL APPARATUS RESOURCES (Pengawasan Kinerja Dalam Mewujudkan Tujuan Pembangunan Sumber Daya Aparatur Daerah) - jarl koagouw; Novrabella Clarashinta Pakasi (Gorontalo Development Review, 2019)
ABSTRACT This paper examines the extent of the implementation of supervision of performance in realizing the objectives of the development of the regional apparatus of North Sulawesi, in addition to knowing the factors that are supporting and inhibiting. This research is a qualitative descriptive study, with interviews. The results of the study show that the factor that is a supporter of the increasing performance of the state civil apparatus is an increase in the quality of human resources, as well as the desire of policy makers to follow up on recommendations issued through performance monitoring. The factor that becomes an obstacle to the obstruction of the objectives of regional development is because there is an unfair sense due to the absence of rewards and punishment. In addition to ignoring recommendations on the results of supervision of performance, the continued practice of collusion and nepotism in the determination of positions is also a determining factor in hampering the achievement of North Sulawesi's development goals.  ABSTRAK Tulisan ini mengkaji tentang sejauh mana pelaksanaan pengawasan kinerja dalam mewujudkan tujuan pembangunan sumber daya aparatur Daerah Provinsi Sulawesi Utara, disamping itu untuk mengetahui faktor yang menjadi pendukung dan penghambat. Penelitian ini merupakan penelitian deskriptif kualitatif, dengan wawancara. Hasil penelitian menunjukkan bahwa faktor yang menjadi pendukung dari meningkatnya kinerja aparatur sipil negara adalah adanya peningkatan kualitas sumber daya manusia, juga adanya keinginan pengambil kebijakan untuk menindaklanjuti rekomendasi-rekomendasi yang dikeluarkan melalui pengawasan kinerja. Faktor yang menjadi kendala dari terhambatnya tujuan pembangunan daerah adalah karena adanya rasa tidak adil disebabkan tidak adanya penghargaan (reward) dan hukuman (punishment). Selain itu mengabaikan rekomendasi hasil pengawasan kinerja, masih adanya praktek kolusi dan nepotisme dalam penentuan jabatan juga menjadi faktor penentu dari terhambatnya pencapaian tujuan pemabangunan Sulawesi Utara.